Teaching Non-Western Students about Western Culture: Western Values Considered within a Global Context - Adrienne Cochran (Networks: An Online Journal for Teacher Research, 2002)
Are we gonna live together - together are we gonna live? (Lee, 1989) These are the words spoken by radio DJ Mister Señor Love Daddy at the end of Spike Lee's film, Do the Right Thing. The previous night the police had brutally killed an African-American, which in turn, led to the looting and destruction of the neighborhood pizzeria. This film is rife with the tensions of several ethnic groups living together in close proximity. A few events of the past two years have given me a deeper understanding of the DJ's words.